Fatigue symptoms in Sri Lanka Navy personnel deployed in combat areas - Hanwella, Raveen; Jayasekera, N.E.L.W.; De Silva, V.A. (Ceylon Medical Journal, 2014)
Objectives: The objective was to study the prevalence of fatigue symptoms among Special Forces and regular forces military personnel deployed in combat areas and to explore factors associated with fatigue symptoms. Methods: This is a cross sectional study of representative samples of Sri Lanka Navy Special Forces and regular forces deployed in combat areas continuously for at least one year. Fatigue was measured using a 12 item fatigue scale. Symptoms of common mental disorder were identified using the General Health questionnaire 12 (GHQ-12). Multiple physical symptoms were elicited using a checklist of symptoms. PTSD was diagnosed using the 17-item National Centre for PTSD checklist civilian version (PCL-C). Results: Sample consisted of 259 Special Forces and 412 regular navy personnel. Prevalence of fatigue over the last month was 13.41% (95% CI 10.83-16.00). Prevalence was significantly less in the Special Forces (5.4%) than in the regular forces (18.4%) [OR 0.38 (95% CI 0.17-0.82)]. Only two types of combat exposure “thought I might be killed” and “coming under mortar, missile and artillery fire” were significantly associated with fatigue symptoms. Fatigue was strongly associated with symptoms of common mental illness [adjusted OR 12.82 (95% CI 7.10-23.12)], PTSD [adjusted OR 9.08 (95% CI 2.84-29.0)] and multiple somatic symptoms [adjusted OR 9.85 (95% CI 5.42-17.9)]. Fatigue was significantly associated with functional impairment. Conclusions: Prevalence of fatigue was significantly lower in the Special Forces despite high combat exposure. Fatigue was associated only with indicators of intense combat exposure. Fatigue caused significant functional impairment even after adjusting for psychological morbidity.
Keywords: fatigue; military personnel; Special Forces; combat; Sri Lanka